Evidence on the adoption of Artificial Intelligence: The role of skills shortage - Paolo Carioli; Dirk Czarnitzki; Gastón P. Fernández (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Artificial Intelligence (AI) is considered to be the next general-purpose technology, with the potential of performing tasks commonly requiring human capabilities. While it is commonly feared that AI replaces labor and disrupts jobs, we instead investigate the potential of AI for overcoming increasingly alarming skills shortages in firms. We exploit unique German survey data from the Mannheim Innovation Panel on both the adoption of AI and the extent to which firms experience scarcity of skills. We measure skills shortage by the number of job vacancies that could not be filled as planned by firms, distinguishing among different types of skills. To account for the potential endogeneity of skills shortage, we also implement instrumental variable estimators. Overall, we find a positive and significant effect of skills shortage on AI adoption, the breadth of AI methods, and the breadth of areas of application of AI. In addition, we find evidence that scarcity of labor with academic education relates to firms exploring and adopting AI.
Keywords: J63; M15; O14; 330; Artificial Intelligence; skills shortage; CIS data